Alpha emitter radium-223 in patients with metastatic castration-resistant prostate cancer: A cost-utility analysis - Zeng, Xiaohui; Liu, Qiao; Tan, Chongqing; Wan, Xiaomin; Wang, Yunhua; Ma, Xiaowei (Frontiers in Pharmacology, 2022)
Objective: To assess the cost-effectiveness of radium-223 dichloride for patients with metastatic castration-resistant prostate cancer (mCRPC) in China. Materials and Methods: A Markov model was developed to estimate the long-term health and economic outcomes of radimu-223 plus best-standard care (BSC) treatment and BSC only for bone mCRPC patients over a lifetime horizon. The patients and intervention were modeled according to the ALSYMPCA trial. Costs were collected from a Chinese health system perspective. Utility values were derived from the published literature. The base-case model results were quality-adjusted life year (QALY), total cost, and incremental cost-utility ratio (ICUR). Uncertainty analyses were performed to assess the robustness of our conclusions. Results: Compared with the BSC arm, Radium-223 achieved an excess 0.344 -QALYs- with an incremental cost of $29,459, resulting in an ICUR of $85,647 per QALY. The probability of Ra-223 being cost-effective for the patients with bone mCRPC was sharply low (< 0.5%) at willingness-to-pay threshold of $38,136/QALY. Uncertainty analyses revealed that the model is robust to all the input parameters. Conclusion: Radium-223 is unlikely to be cost-effective in patients with bone mCRPC at the current WTP threshold, from a Chinese health system perspective. In affluent areas with a high per-capita GDP, radium-223 therapy may be cost-effective.